Pertimbangan Majelis Hakim Meringankan Hukuman Richard Eliezer Ditinjau Berdasarkan Teori Tujuan Pemidanaan Hukum Yang Berkeadilan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The Application of Justice Collaborator in the crime of premeditated murder is still considered unclear, this is based on the provisions in Law Number 31 of 2014 concerning the Protection of Witnesses and Victims, as well as SEMA Number 4 of 2011 which explains that a witness to a perpetrator who is a worker can appear in a confrontation at certain or special types of cases. These pros and cons reappear because a Justice Collaborator has the right to obtain leniency as a form of legal protection for perpetrator witnesses, even though the perpetrator is an important person in the case yet he is not an intellectual actor. Research shows several regulations governing Justice Collaborators, but they are not yet rigid and have finally expanded their meaning in their application. The provisions regarding the implementation of Justice Collaborator are considered to have an important existence in the criminal system.